Optimized AAV rh.10 Vectors That Partially Evade Neutralizing Antibodies during Hepatic Gene Transfer - Selot, Ruchita; Arumugam, Sathyathithan; Mary, Bertin; Cheemadan, Sabna; Jayandharan, Giridhara R. (Frontiers in Pharmacology, 2017)
The development of an Adeno-associated virus (AAV) vector that can bypass pre-existing immunity in humans is crucial for universal application of this vector system. Among the diverse AAV serotypes, wild type AAVrh.10 has shown sustained hepatic transduction and has the lowest seropositivity in humans. We have evaluated if further modifications to AAVrh.10 at its phosphodegron like regions or predicted immunogenic epitopes could improve its hepatic gene transfer and immune evasion potential. Mutant AAVrh.10 vectors were generated by site directed mutagenesis of the predicted targets. These mutant vectors were first tested for their transduction efficiency in HeLa and HEK293T cells. The optimal vector was further evaluated for their cellular uptake, entry and intracellular trafficking by quantitative PCR and time-lapse confocal microscopy. To evaluate the gene transfer efficacy of the vectors in vivo, C57BL/6 mice were administered with wild-type or optimal mutant AAVrh.10 vectors and the luciferase expression was documented by serial bioluminescence imaging at 14, 30, 45 and 72 days post gene transfer. Vector genome copy number in the liver tissue was determined by a quantitative PCR assay. The optimal AAVrh.10 vector was further evaluated for their immune escape potential, in animals pre-immunized with human intravenous immunoglobulin. Our results demonstrate that a modified AAVrh.10 S671A vector had enhanced cellular entry (3.6 fold), migrate rapidly to the perinuclear region (1 Vs >2 hours for wild type vectors) in vitro, which further translates to modest increase in hepatic gene transfer efficiency in vivo. More importantly, the mutant AAVrh.10 vector was able to partially evade neutralizing antibodies (~27 to 64 fold) in pre-immunized animals. The development of AAVrh.10 vectors with an immunologically inert phenotype augurs well for their potential use in human gene therapy applications.